La importancia de la lactancia materna - Gutiérrez Changoluisa, Adriana Nathaly (2016)
In recent years it has caused an increase in teenage pregnancy and with it a decrease in the practice of breastfeeding, which occurs during the first six months of life infant, is this situation that requires knowledge importance of breastfeeding for mothers put the interest to know about the benefits that feeding breast milk as it's the optimal food for infant development during the first six months of life. The main objective was to determine the importance about breastfeeding as essential to protect the health in a baby, for this reason the advantages offered, the knowledge of breastfeeding the research process that was applied are the surveys and interviews to determine the diagnosis of breastfeeding were conducted to know the importance of breastfeeding, and the main results were mother's who in one way or another do not know the background this topic purposeless and that breastfeeding is important for an emotional bond between mother and child. For this reason proposal it will help to continue maintaining this opportunity for mother’s gestation period of practice breastfeeding from the first day the baby is born, and so improve the quality of life of the infant disease and infections that can affect a child's health.The research was interest to implement the theoretical knowledge is gained for the development and growth of the baby which benefits the health of the mother and child.